Favorable results in ABO‐incompatible renal transplantation without B cell‐targeted therapy: Advantages and disadvantages of rituximab pretreatment. Issue 10 (29th August 2017) - Okada, Manabu; Watarai, Yoshihiko; Iwasaki, Kenta; Murotani, Kenta; Futamura, Kenta; Yamamoto, Takayuki; Hiramitsu, Takahisa; Tsujita, Makoto; Goto, Norihiko; Narumi, Shunji; Takeda, Asami; Morozumi, Kunio; et al.
Abstract: The effectiveness of desensitization with rituximab in ABO‐incompatible renal transplantation (ABO‐I) has been widely reported. However, ABO‐I outcomes are still worse than those of ABO‐identical or ABO‐compatible renal transplantation (ABO‐Id/C). We retrospectively examined the outcomes in consecutive living donor ABO‐Id/C (n = 412) and ABO‐I (n = 205) cases to elucidate the causes of inferiority in ABO‐I. ABO‐I cases included recipients treated with rituximab (RIT, n = 131), splenectomy (SPX, n = 21), or neither because of low anti‐A/B antibody titers (NoR/S, n = 53). Graft survival, infection, and de novo HLA antibody production were compared for ABO‐I and ABO‐Id/C, followed by stratification into RIT and NoR/S groups. Propensity score‐based methods were employed to limit selection bias and potential confounders. Overall graft survival for ABO‐I was significantly lower than that for ABO‐Id/C (92.8% vs 97.2% after 5 years, P  = .0037). Graft loss due to infection with ABO‐I was significantly more frequent than that with ABO‐Id/C, whereas acute antibody‐mediated rejection (AMR) caused no graft failure in ABO‐I recipients. Stratified analysis demonstrated significantly higher infection risk with RIT than with NoR/S. Safe reduction or avoidance of rituximab in desensitization protocols might contribute to further improvement of ABO‐I outcome.